2015
DOI: 10.1093/ckj/sfu145
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a quality and safety checklist for haemodialysis sessions

Abstract: BackgroundPatient survival and quality of life depend on each haemodialysis session being performed without fault. Monthly assessments of dialysis dose adequacy often fall short of this. This study reports the results of a feasibility study for the achievement of improved safety and quality in a haemodialysis session with the implementation of a 15-point checklist.MethodsFifteen quality indicators were compiled and tested in a Portuguese dialysis clinic from 1 February 2012 to 30 June 2013. The checklist was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
(17 reference statements)
1
11
0
3
Order By: Relevance
“…The results of our study are in keeping with the results of two other hemodialysis checklist feasibility studies [ 10 , 11 ]. The checklists by Marcelli et al [ 10 ] and Galland et al [ 11 ] were found to be feasible and acceptable for use among their study participants. The acceptance of our checklist by nursing staff and patients may be related to the common features it shares with the aforementioned checklists, with 70–80% of the items similar across all three checklists.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of our study are in keeping with the results of two other hemodialysis checklist feasibility studies [ 10 , 11 ]. The checklists by Marcelli et al [ 10 ] and Galland et al [ 11 ] were found to be feasible and acceptable for use among their study participants. The acceptance of our checklist by nursing staff and patients may be related to the common features it shares with the aforementioned checklists, with 70–80% of the items similar across all three checklists.…”
Section: Discussionsupporting
confidence: 88%
“…Another important difference is the format of the checklist. The Hemo Pause checklist was designed to be completed manually as the hemodialysis session progresses, whereas the checklist by Marcelli et al [ 10 ] was completed automatically from device monitors and electronic records rather than being physically checked by a person. This difference may be important, since it is the act of completing the checklist that affects behavior, not using the checklist as a means of data collection or assurance [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tool II: Observational Checklist: Which containing Safety and Quality Checklist in Hemodialysis session: it is adapted from [1,14] to assess level of nurse's practice regarding prevention of adverse events at hemodialysis. It contains 39 items divided into three levels.…”
Section: Data Collectionmentioning
confidence: 99%
“…The study by Marcelli et al [ 7 ] describes the use of a dialysis checklist in a dialysis facility in Portugal. The checklist included 15 items encompassing pre-session safety checks, session initiation checks and post-session quality checks.…”
mentioning
confidence: 99%